The Impact of Policy Application on Milk Industry to The Social Welfare - Priyanti, Atien; Rindayati, W; Rumagit, G A J (Indonesian Animal Sciences Society, 2004)
An assessment to identify and qualify the impact of policy application on milk industry in Indonesia has been carried out to estimate the extent of profit and loss obtained by milk industry producers, including the government . The development of milk industry in Indonesia in the last decade has been very significant supported by the government. Application policy of BUSEP ratio since 1982 was very powerful in order to give protection to dairy farmers, this consider a non-tariff barrier policy. Nevertheless, since the Gol has signed the memorandum of understanding with IMF in January 1988 of the elimination for nontariff barrier policy, the application of BUSEP ratio has also denied. Through comparative static analysis, it could be shown that the application of BUSEP ratio decreased economic development due to decreasing consumer surplus, increasing producer surplus and decreasing net social welfare. Fiscal policy such as application of import tariff may also decrease the economic development, however it could decrease the import volume, with the assumption of unchanged export volume, it results trade surplus. The application of 5% import tariff of milk may decrease consumer surplus, increase producer surplus and government revenue from tax along with its dead weight loss. Application of import tariff from the government has resulted decreasing net social welfare. Key words: Policy analysis, milk industry, producer and consumer surplus, and social welfare